Analysis New Public Service: Case study on the TNI Manunggal Building a Village (TMMD) - Dedyk Wahyu Widodo; Bintoro Wardiyanto; Erna Setijaningrum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the application of New Public Management (NPM) principles in the implementation of the TNI Manunggal Membangun Desa (TMMD) program by the Indonesian Army and to examine the dynamics and challenges of public service values through the perspective of New Public Service (NPS). This study uses a qualitative approach with a case study on the implementation of TMMD in Kedondong Village, Sidoarjo Regency. Data was collected through analysis of TMMD activity reports and interviews with officials from Kodim 0816/Sidoarjo, village officials, and community members who benefited from the program. The results of the study show that NPM principles, such as structured planning, organizational discipline, results orientation, and activity control, play an important role in ensuring the effectiveness of TMMD implementation in the context of a hierarchical military organization. However, the success of the program is not only determined by the achievement of outputs, but also by public service values that are in line with the NPS paradigm, such as community participation, orientation towards public interests, strengthening civic values, service and assistance practices, and the social impact felt by the community. These findings indicate that TMMD governance reflects a hybrid model between NPM and NPS, in which organizational efficiency and performance are complemented by values of service to citizens. This study contributes to the development of public administration studies by enriching the understanding of the application of public management paradigms in the context of civil-military relations.